The world's most remote community service? Partnership working and building community capacity on the British Overseas Territory Island of St Helena - Campbell, Fiona (Probation journal, 2024)
Measuring just 47 square miles and 1950 km from its nearest neighbour, St Helena is a British Overseas Territory in the South Atlantic with a population of approximately 4500. Working in this remote setting is one of the world's smallest probation services delivering a range of interventions including community service. In this practice note the authors explore the sustained, successful partnership between St Helena Island Probation Service and the St Helena National Trust. This partnership not only provides meaningful community service placements which support vital conservation work, but simultaneously contributes to an individual's journey towards desistance through enhancing employability and supporting positive community reintegration.